Rhombohedral superlattice structure and relaxor ferroelectric behavior of (Pb0.70Ba0.30)ZrO3 ceramics - Pokharel B.P.; Ranjan R.; Pandey D.; Siruguri V.; Paranjpe S.K. (My University, 2025)
Superlattice reflections observed in the neutron powder-diffraction patterns of (Pb0.80Ba0.20)ZrO3 (PBZ20) and (Pb0.70Ba0.30)ZrO3 (PBZ30) are explained in terms of doubled rhombohedral cell (R3c). A Rietveld analysis of the neutron data reveals that the displacements of Pb2+/Ba2+ and Zr4+ decrease with increasing Ba2+ content while the thermal parameter for Pb2+/Ba2+ increases and becomes similar to ferroelectric relaxors. Dielectric studies indeed confirm relaxor behavior in PBZ30 with Vogel-Fulcher type relaxational freezing. © 1999 American Institute of Physics.